(untitled) (Estima – Brazilian Journal of Enterostomal Therapy, 2025)
Objective: To identify the point prevalence of pressure injuries (PI) and medical device-related pressure injuries (MDRPIs), the associated demographic and clinical factors, and to describe them in terms of classification, site, and number. Method: A cross-sectional study conducted in the Intensive Care Unit (ICU) of two public cardiology hospitals. Demographic and clinical data, along with information on PI, were collected from 123 patients aged 18 years old or older admitted to the ICU, through physical examination and medical records. Descriptive, univariate and multivariate analyses were used, as well as calculation of point prevalence. Results: The point prevalence of PIs was 46.34% (51/123 patients) and that of MDRPIs was 8.94% (11/123 patients). The most frequent anatomical site of PI was the sacral region (38.02%), classified as stage 2 (18.30%). Ears (7.03%) and stage 2 (78.57%) were the most frequent in MDRPI. Multivariate analysis indicated that patients using moisturizing creams, with a Braden score <17.5 and systolic blood pressure <134 mmHg were associated with the development of PI. Conclusion: The study contributed to the knowledge of the epidemiological profile of patients with PI admitted to a cardiac ICU, assisting the nursing team in planning and implementing preventive care.